Intraoperative Electrocochleography in Patients With Menière's Disease Undergoing Endolymphatic Sac Decompression and Shunt Surgery. Issue 9 (October 2019) - Mattingly, Jameson K.; Zhan, Kevin Y.; Hiss, Meghan M.; Harris, Michael S.; Dodson, Edward E.; Moberly, Aaron C.; Adunka, Oliver F.; Riggs, William J.
Abstract : Hypothesis: Objective physiologic changes measured using electrocochleography at the round window (ECOG RW ) are observable during endolymphatic sac decompression and shunt surgery (ELS). Background: Limited effective treatment options are available to patients with Menière 's disease (MD) who have failed conservative management, experience persistent vertigo symptoms, and have substantial residual hearing. ELS is a feasible therapeutic option for these patients. However, the efficacy of this procedure has been questioned, and objective measures assessing inner ear physiologic alterations are lacking. Methods: ECOG RW was measured in patients with MD undergoing ELS. Stimuli consisted of tone bursts (250, 500, 1000, 2000, 4000 Hz) and 100 μs broadband clicks at various intensities (60–90 dB nHL). Cochlear microphonic (CM), summation potential (SP), compound action potential (AP), SP:AP ratio, and CM harmonic distortions were measured. Results: ECOG RW was completed in 18 patients. The mean SP magnitude at 500 Hz changed significantly from −7.1 μV before to −5.1 μV after ELS ( p  < 0.05). However, the mean SP:AP ratio in those tested (n = 13) did not significantly change after ELS. CM harmonic magnitudes remained unchanged from pre- to post-ELS (n = 12) across all frequencies. Conclusion: ECOG RW allows detection of acute electrophysiological changes in the cochlea. However, our results indicate only small objective changes in the low-frequency SP magnitude (500 Hz) immediately after ELS, but not in other frequencies or measures tested (CM, SP:AP, CM harmonic distortions). These results suggest minimal electrophysiological changes occur in the cochlea as a result of ELS.